2015
DOI: 10.1111/epi.13218
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of temporal and spectral dynamics of pathologic high‐frequency oscillations (pHFOs) during epileptogenesis

Abstract: Objective In temporal lobe epilepsy (TLE) pathological high frequency oscillations (pHFOs, 200–600 Hz) are present in the hippocampus, especially the dentate gyrus (DG). The pHFOs emerge during a latent period prior to the onset of spontaneous generalized seizures. We used a unilateral suprahippocampal injection of kainic acid (KA) mouse model of TLE to characterize the properties of hippocampal pHFOs during epileptogenesis. Methods In awake head-fixed mice, 4–14 days after KA-induced status epilepticus (SE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Increased HFO rates after SE have been widely observed in experimental models of TLE, in HP, dentate gyrus, and entorhinal cortex . Bragin et al suggested that HFOs in both the ripple and FR ranges can be pathological after SE .…”
Section: Discussionmentioning
confidence: 99%
“…Increased HFO rates after SE have been widely observed in experimental models of TLE, in HP, dentate gyrus, and entorhinal cortex . Bragin et al suggested that HFOs in both the ripple and FR ranges can be pathological after SE .…”
Section: Discussionmentioning
confidence: 99%
“…1; 67 More recently, investigators used a unilateral supra-hippocampal injection of kainic acid in mice that produced cell loss in the ipsilateral CA3, CA1, and hilar regions, as well granule cell dispersion and mossy fiber sprouting within two weeks after the injection. 68 The contralateral hippocampus, however, was relatively unaffected. Overall the histopathological changes seen in these experiments along with the appearance of seizures from the injected hippocampus reproduced several aspects of human TLE.…”
Section: Hfos In Models Of Epilepsymentioning
confidence: 97%
“…Kaplan-Meir curves show 5-year seizure freedom for patients with unilateral mesial temporal sclerosis (MTS) is 72%, lesional MRI excluding MTS is 70%, and normal MRI temporal lobe epilepsy and extratemporal lobe epilepsy is ~60% [62,63] and 28% [64 ▪▪ ], respectively. Normal MRI patients have worse long-term outcomes, and for all patients the risk of seizure recurrence extends well beyond 1 year.…”
Section: Figurementioning
confidence: 99%
“…2 [6163]). There is evidence in rodent epilepsy models that pHFOs (200–600 Hz) are a biomarker of epileptogenesis [59,64 ▪▪ ]. This is a critically important topic for epilepsy surgery, given that many patients that are initially seizure free suffer late recurrence of their seizures.…”
Section: Introductionmentioning
confidence: 99%